The effectiveness of using various types of stimulating substances for the propagation of clonal rootstocks of pome crops in arid zone conditions - N. I. Matveeva (Аграрная наука Евро-Северо-Востока, 2024)
The purpose of the research is to identify the effectiveness of the use of various stimulating substances on the economic and biological parameters of plants of clonal apple rootstocks in the conditions of the arid zone of the Northern Caspian Sea (Astrakhan region). The objects were apple tree clonal rootstocks, scion and rootstock combinations. In the mother plantation of vertical layering, 10 breeding forms of rootstocks selected by various scientific institutions were studied. The control was the M series rootstocks, widely used and adapted in the south of Russia: M-9 for dwarf ones, M-26 for semi-dwarf ones, MM-106 for medium-sized ones. In a vertical mother plantation, there were studied variants for leaf treatments with Etamon Bio and Aminovit (control - treatment with water). Average for 2021–2023 foliar treatments significantly contributed to the high yield of first-grade rootstocks for rootstock forms 87-7-12 – 35.4 %; ‘Ural 8’ – 18.0 %; M-26 – 15.0 %; ‘Ural 5’ – 14.0 %; rootstock ‘Malysh Budagovskogo’ – 20.3 % in the variant with Etamon Bio treatment. In the variant with Aminovit treatment, the most number of first-grade layerings were obtained from the rootstock form 87-7-12 – 36.3 %; ‘Ural 8’ – 19.5 %; ‘Malysh Budagovskogo’ – 23.0 %. Foliar feeding with Etamon Bio and Aminovit had a positive effect on the length of the root system, an increase in the diameter of the trunk and an increase in the height of the rootstocks. In the first field of the nursery, the varieties were grafted onto rootstocks of varying vigor. The drugs for study were root formation stimulants Zircon; Ribav Extra; Kornevin. As a result, in comparison with the control, the survival rate of all rootstocks treated in the Zircon root formation stimulator was 100 %.